Thiamine pyrophosphokinase deficiency: report of two Chinese cases and a literature review - Zhao, Dan; Liu, Ming; Jiang, Huafang; Song, Tianyu; Xu, Chaolong; Duan, Xin; Duan, Ruoyu; Xu, Han; Liu, Zhimei; Fang, Fang (Frontiers in Pediatrics, 2023)
Thiamine pyrophosphokinase (TPK) deficiency, is a rare autosomal recessive disorder of congenital metabolic dysfunction caused by variants in the TPK1 gene. TPK1 variants can lead to thiamine metabolic pathway obstacles, and its clinical manifestations are highly variable. We describe two cases of TPK deficiency with completely different phenotypes and different therapeutic effects, and 26 cases of previously reported were retrospectively reviewed to improve our understanding of the clinical and genetic features of the disease. Patients with TPK deficiency present with ataxia, dysarthria, dystonia, disturbance of consciousness, seizures, and other nervous system dysfunction. Different gene variant sites may lead to different clinical features and therapeutic effects. Gene analysis is important for the diagnosis of TPK deficiency caused by TPK1 variants, and thiamine supplementation has been the mainstay of treatment for TPK deficiency to date.